Practical sustainability strategies : how to gain a competitive advantage - Avlonas, Nikos, 1969- (Wiley, 2014)
This book provides tested and proven practical strategies that make it possible for organizations to develop, maintain, or extend their competitive advantage without causing harm to the environment and society. It explains how to set goals and objectives and then monitor, measure, and report on progress towards achieving corporate social responsibility and environmental sustainability. Readers will discover that this can all be accomplished while, at the same time, improving bottom-line profitability. Case studies based on the authors' research and fieldwork illustrate how leading companies have implemented each of the sustainability strategies discussed in the book. There is also an appendix with additional case studies exploring various aspects of business practices and sustainability. - Resumé vydavatele